Valkoisia kanervakukkia - Roos, Mathilda, 1852-1908; Krohn, Aune, 1881-1967 (Salt Lake City, UT : Project Gutenberg, 2012)
"Valkoisia kanervakukkia" by Mathilda Roos is a novel written in the early 20th century. This work likely explores themes of love, sorrow, and the beauty of nature through the experiences of its characters, most notably focusing on a young woman and her interactions with her community. The opening of the novel paints a vivid picture of a serene, natural landscape where a young woman walks through fields during a summer morning, filled with lively descriptions of blooming flowers and the sounds of nature. As she awaits a meeting with someone special, her thoughts reflect a blend of anticipation and impatience. The narrative introduces us to various characters, including the caring "kalaasi-Lotta," who looks after others, and the gentle and introspective Ingrid Medin, who faces challenges due to her health. The young pastor, Nils Martin, also emerges as a significant character who is drawn to Ingrid's inner beauty and resilience, hinting at a deeper connection that may unfold throughout the story. (This is an automatically generated summary.)
Release date is 2012-05-22
Produced by Tapio Riikonen
Keywords: Swedish fiction -- Translations into Finnish